Examining tabloidization in The Straits Times. - Quak, Angeline Yan Xin. (2012)
The aim of this study is to explore whether there is an increasing trend towards tabloidization in The Straits Times in Singapore. The stories being examined in this study were on the Indian Ocean Earthquake and Tsunami, 2004 and the Japan Earthquake and Tsunami, 2011. A keyword analysis was conducted to determine the presence of tabloidization in The Straits Times. The keywords were also used in an interpretative study of the text to determine the presence of tabloidization. Of a combined total of 792 keywords listed, only 27 could be categorised as being tabloidized. This study concludes by saying that there is very little tabloidization in The Straits Times with regards to its reporting on disaster stories.